Effects of metabolic cancer therapy on tumor microenvironment - Hyroššová, Petra; Milošević, Mirko; Škoda, Josef; Vachtenheim Jr, Jiří; Rohlena, Jakub; Rohlenová, Kateřina (Frontiers in Oncology, 2022)
Targeting tumor metabolism for cancer therapy is an old strategy. In fact, historically the first effective cancer therapeutics were directed at nucleotide metabolism. The spectrum of metabolic drugs considered in cancer increases rapidly – clinical trials are in progress for agents directed at glycolysis, oxidative phosphorylation, glutaminolysis and several others. These pathways are essential for cancer cell proliferation and redox homeostasis, but are also required, to various degrees, in other cell types present in the tumor microenvironment, including immune cells, endothelial cells and fibroblasts. How metabolism-targeted treatments impact these tumor-associated cell types is not fully understood, even though their response may co-determine the overall effectivity of therapy. Indeed, the metabolic dependencies of stromal cells have been overlooked for a long time. Therefore, it is important that metabolic therapy is considered in the context of tumor microenvironment, as understanding the metabolic vulnerabilities of both cancer and stromal cells can guide new treatment concepts and help better understand treatment resistance. In this review we discuss recent findings covering the impact of metabolic interventions on cellular components of the tumor microenvironment and their implications for metabolic cancer therapy.